2019
DOI: 10.3390/ijerph16071112
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Studies Conducted in Australia: A Scoping Review

Abstract: Health literacy (HL) is an essential component of various literacies mentioned in the field of health and education, including cultural, technological, media and scientific literacies. It is important for motivating higher consumer engagement. We aimed to review previous studies of HL in Australia to inform future studies, extend current knowledge and further enhance HL. Using search strings, a systematic search of four databases (i.e., MEDLINE; Embase; CINAHL and Eric) was carried out. A Preferred Reporting I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 93 publications
(242 reference statements)
0
43
0
Order By: Relevance
“…Therefore, it is all the more important to analyze the difficulties in navigation, and even more so the HL-NAV, necessary to better deal with it, in more detail. So far—as the literature analysis and comparable reviews on health literacy have shown [ 57 ]—this has been done only very cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is all the more important to analyze the difficulties in navigation, and even more so the HL-NAV, necessary to better deal with it, in more detail. So far—as the literature analysis and comparable reviews on health literacy have shown [ 57 ]—this has been done only very cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that there is a social gradient in adolescent health literacy, 23,24 which in turn leads to health promotion outcomes. Adolescents with high health literacy levels are more likely to have health‐promoting behaviours, communicate effectively with health professionals, and perceive their health status as good 4,5,24 . Due to the small sample size, we did not test the reliability and validity of the three health literacy instruments and did not investigate the relationship between adolescent health literacy and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…An overall rating (from 0 to 1) was assigned to every study with higher numerical ratings indicating higher quality. This checklist had already been used in previous reviews to assess the quality of included studies (Choudhry et al, 2019; Munawar, Kuhn, & Haque, 2018; Wassenaar, Schouten, & Schoonhoven, 2014). The lowest quality rating of both the quantitative and qualitative studies included in this review was determined to be 0.55.…”
Section: Methodsmentioning
confidence: 99%